Species diversity of bats in the Skole Beskids National Nature Park - Chaika, Y.; Kusnezh, O. (Theriologia Ukrainica, 2018)
In total, 21 species of bats were found in the Skole Beskids National Nature Park. Among them, six species were recorded in the territory of the Park form the first time: Rhinolophus ferrumequinum, Myotis brandtii, M. alcathoe, M. dasycneme, Plecotus austriacus, and Nyctalus leisleri. Additionally, R. ferrumequinum was recorded in Lviv region for the first time as well. During the summer, we observed 16 species of bats in the Park. The abundance of bats during this season was not very high, and the places with their most explicit activity were the Zhuravlyne and Polianetske lakes. It was established that 10 species take part in the fall swarming. The most abundant species during swarming was Myotis myotis. The period of swarming lasted from the beginning of September to the end of October. During the period of hibernation, 11 species of bats were observed. The bats were found in 5 of 15 examined caves on Kliuch mountain. The period of hibernation during the 2015/2016 season lasted from the third decade of November to the third decade of March. НПП «Сколівські Бескиди» виявлено 21 вид рукокрилих. Протягом досліджень було виявлено шість нових для території Парку види: Rhinolophus ferrumequinum, Myotis brandtii, M. alcathoe, M. dasycneme, Plecotus austriacus, Nyctalus leisleri. Rhinolophus ferrumequinum виявлений вперше для території Львівської області. Під час літнього періоду у НПП трапляється 16 видів рукокрилих. Чисельність кажані протягом цього періоду не висока, місця найбільшої активності оз. Журавлине, оз. Полянецьке. Встановлено, що в осінньому роїнні беруть участь представники 10 видів рукокрилих. Найчисельніший вид на роїнні — M. myotis. Період роїння тривав з початку вересня до кінця жовтня. У період гібернації відмічено представників 11 видів рукокрилих. Кажани виявлені нами у 5 із 15 обстежених печер г. Ключ. Період зимівлі у сезон 2015/2016 рр. тривав із ІІІ декади листопада до ІІІ декади березня.